In-situ measurement and formability improvement in stamping of high strength steel and titanium alloy sheets - Zamzuri, Hamedon (2014)
The information and visualization of deformation behaviour of the high strength steel sheet during the stamping process are useful for designing tools and processes in metal forming industry. However, it is not easy to measure the deformation behaviour during stamping processes because a deforming sheet is generally surrounded with complicated tools during a stamping operation, and thus, application of sensors for the in-situ measurement has been still limited. Borescopes consisting of a small camera and a flexible cable have possibility of application to forming processes as an imaging sensor and the installation of the borescopes inside tools enables the in-situ measurement. The three-dimensional deformation behaviour of the sheet and tools were successfully measured using borescope. The use of the ultra-high strength steel sheets for automobile body-in-white parts is increasing, whereas it is not easy to form the the ultra-high strength steel sheets. A gradually contacting punch was developed to reduce a tensile stress during the forming process with controlling a stress state around sheared edges undergoing plastic deformation. However, the punch stroke increased for stretch flanging, i.e. increases in production time and cost. In order to reduce the punch stroke, a 2-stage process using a recessed punch was developed for stretch flanging. In order to increase the safety of cars, the structure of body members was optimized. Front rail hollow sections act as an energy absorber during collision, and are permanently deformed in order to absorb the kinetic energy during the crash. These hollow sections typically joined by resistance spot welding have insufficient energy absorption, because the joint are not continuous. In order to overcome this problem, the hollow section is joined by hemming. Since the hollow section having hemmed joins is overlapped, the strength is increased in comparison with resistance spot welded joins. Although titanium alloy sheets are widely used for airplane parts due to its properties of high strength at high temperatures, low density and high corrosion resistance, ductility of the titanium alloy sheets is very low, and thus it is difficult to form the titanium alloy sheets at room temperature. The sheets are generally formed at elevated temperatures. Hot hat-shaped bending of the Ti-6Al-4V titanium sheet using the resistance was carried out. The titanium alloy sheet was successfully formed at the elevated temperatures, the bending load was reduced and the springback and oxidation are prevented.